Do vaccinations influence the development of Alzheimer disease? - Avram S. Bukhbinder; Yaobin Ling; Kristofer Harris; Xiaoqian Jiang; Paul E. Schulz (Taylor & Francis Group, 2023)
A growing literature supports a protective association between vaccines targeting an array of pathogens (e.g., influenza, pneumococcus, herpes zoster) and the risk of Alzheimer disease (AD). This article discusses the potential underlying mechanisms for this apparent protective effect of immunizations against infectious pathogens on the risk of AD; explores the basic and pharmacoepidemiologic evidence for this association, with particular attention paid to important methodological variations among the epidemiologic studies; and reviews the remaining uncertainties regarding the effects of anti-pathogen vaccines on Alzheimer disease and all-cause dementia, with recommendations for future directions to address those uncertainties.